Sustainability and energy transition – Perspectives for an integrated approach to the built heritage - Davide Del Curto; Andrea Garzulino; Anna Turrina (Agathón)
The energy transition of the built environment is a fundamental process for reducing greenhouse gas emissions and mitigating the effects of climate change. Addressing this challenge requires a comprehensive and multidisciplinary approach that considers technological, architectural, environmental, social and cultural aspects with the same level of interest. However, the debate focuses on new zero-emission buildings, while policies such as the Italian 110% Superbonus have promoted retrofitting interventions aimed exclusively at achieving specific energy characteristics. The contribution discusses the importance of attributing the correct role to sustainability, clarifying the starting point and highlighting the results achieved through often conflicting approaches.